Designing Problem-Based E-Learning to Foster Critical Thinking and Motivation: A Feasibility and Practicality Study - Christina Ismaniati; Enang Syamsudin; Nurul Inayah Khairaty (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to: (1) develop feasible, problem-based e-learning media for fifth-grade students; (2) evaluate its practicality in social studies learning; and (3) examine its effectiveness in enhancing critical thinking and learning motivation. Using the ADDIE model, the research involved 55 fifth-grade students at SDIT Salman Al-Farisi II. Data were collected through interviews, questionnaires, tests, and motivation scales. Experts validated the media as highly feasible (media: 74; content: 60) and considered highly practical based on teacher and student responses. Effectiveness testing revealed that the experimental group using the e-learning media achieved higher N-Gain scores in critical thinking (0.72, high) and learning motivation (0.53, moderate) than the control group (0.48 and 0.21, respectively). MANOVA analysis confirmed significant differences between groups in both variables (Wilks' Lambda = 0.118, F = 7.715, p = 0.000). These results demonstrate the statistical effectiveness of the problem-based e-learning approach. This study contributes a validated, interactive e-learning design that integrates problem-based strategies to foster 21st-century skills in elementary education. The findings provide practical insights for educators and researchers seeking to enhance student engagement, critical thinking, and learning motivation through digital learning environments.